DAMPAK KEBERADAAN TAMAN GENANG GENIS TERHADAP PEREKONOMIAN MASYARAKAT DI KOTA SUMBAWA BESAR - Manulang, Tata Imas; Fitriyani, Ika (Jurnal Ekonomi & Bisnis, 2024)
This study aims to determine the difference in people's income in Sumbawa Besar City before and after the existence of Genang Genis Park Sumbawa Besar. The type of this study was comparative study. The type of data used was quantitative data obtained directly from research sources, namely traders at the Genang Genis Park Sumbawa Besar. The number of traders at Genang Genis Park Sumbawa Besar who were sources for this study was 20 people. Data collection in this study used structured interview techniques with interview guidelines. Data analysis in this study used the two-average difference test technique. The results of study showed that there is a positive and significant difference in the level of income of traders before and after the existence of Genang Genis Park Sumbawa Besar. Traders' income experienced a significant increase after the existence of Genang Genis Park Sumbawa Besar compared to previous income. Thus, it can be stated that the existence of Genang Genis Park Sumbawa Besar had a big impact on increasing the income earned by traders in Sumbawa Besar City.